2017
DOI: 10.19182/bft2017.331.a31323
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Mechanical and Natural Durability Properties of Wood From Reforestation Pinus Halepensis Mill. In the Mediterranean Basin

Abstract: Pinus halepensis Mill. was introduced into regions with a Mediterranean cli- mate as an ornamental tree, and is now often found in parks and gardens. At pre- sent, Aleppo pine (Pinus halepensis Mill.) forests cover approximately 2,500,000 ha in the Mediterranean Basin, mostly at low altitudes (less than 500 m) and along the coast. It has become naturalized outside cities in North Africa to the extent that it is now listed as an invasive species there. Because of its size (over 15 m in height and 30 cm in diame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
(3 reference statements)
2
6
0
Order By: Relevance
“…Thus, it can be verified that the values obtained for this property are valid because they are below the bending values but close to them. Finally, the average value of the density remains within the interval reported by [5,6].…”
Section: Morc (Mpa)supporting
confidence: 52%
See 2 more Smart Citations
“…Thus, it can be verified that the values obtained for this property are valid because they are below the bending values but close to them. Finally, the average value of the density remains within the interval reported by [5,6].…”
Section: Morc (Mpa)supporting
confidence: 52%
“…Figure 2 shows the pattern arranged on the samples to be tested. To validate the quality of the applied speckling pattern, the mean intensity gradient (MIG) [48] was calculated using Equation (6). This parameter enables quantitative evaluation of the speckle; higher values correspond to a better distribution of the gray scale, thus implying lower errors in the results of the digital correlation of images.…”
Section: Equipment and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study showed increase in the durability of the tested textiles; moreover, the textiles were reinforced. HAMID R. TAGHIYARI, REZA MAJIDINAJAFABADI and REZA VAHIDZADEH Cellulosic materials are vulnerable to different wood-deteriorating fungi and molds (Elaieb et al 2017, Morias et al 2018. Metal and mineral nano-materials have also been used to improve biological resistance of wood and wood composites to different fungi (Karimi et al 2013, Taghiyari et al 2014a, b, Bari et al 2015, 2017, and to improve many properties in different materials (Pethig 2017, Sandeep et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The easy adaptation of P. halepensis to various eco-climatic conditions and poor soils makes the species a desired tree for reforestation programs in Mediterranean countries (Elaieb et al 2017, Liphschitz & Biger 2001, Montero et al 2001, Sghaier & Ammari 2012. Silvicultural treatments of the species have been investigated in different countries (Montero et al 2001) for forest management.…”
Section: Introductionmentioning
confidence: 99%